2006
DOI: 10.1097/01.gim.0000204472.25153.8d
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of medium chain acyl-CoA dehydrogenase deficiency: An update

Abstract: The most common fatty acid oxidation disorder, medium chain acyl-CoA dehydrogenase deficiency (MCADD), has become the focal point for the adoption of tandem mass spectrometry to detect it and related inborn errors of metabolism. This article updates a human genome epidemiology review of MCADD published in 1999. The focus of this update is on epidemiologic parameters rather than mutations associated with MCADD. Currently available information from screening studies on the frequency of detection of MCADD in newb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(128 citation statements)
references
References 43 publications
7
119
1
1
Order By: Relevance
“…It has been reported that the incidence of MCADD is similar to that of phenylketonuria (1:10,000 live newborns) or even higher (Grosse et al 2006). In our population, the frequency is 1/18,847 live births.…”
Section: Discussionsupporting
confidence: 63%
“…It has been reported that the incidence of MCADD is similar to that of phenylketonuria (1:10,000 live newborns) or even higher (Grosse et al 2006). In our population, the frequency is 1/18,847 live births.…”
Section: Discussionsupporting
confidence: 63%
“…MCAD deficiency (OMIM #201450) is the most well studied FAO disease [107], with the majority of symptomatic MCAD deficiencies thought to result from a common point mutation (985A>G) in ACADM [108]. Clinical presentations include hypotonia, Reye-like Syndrome, seizures, apnoea, hepatomegaly, fever, vomiting, diarrhoea and coma [109].…”
Section: Disorders Of Fao Enzymesmentioning
confidence: 99%
“…Medium-chain acyl-CoA dehydrogenase deficiency (MCADD) is the most common inborn error of fatty acid oxidation, which affects about 1:20,000 to 1:8,000 newborns (Andresen et al 2001;Grosse et al 2006;Saudubray et al 2012). It is included in many newborn screening programmes worldwide (National Newborn Screening and Genetics Resource Center, Austin, Texas; Bundesausschuss 2005; Wilcken et al 2007).…”
Section: Introductionmentioning
confidence: 99%